Evaluation of local injection of Acrylic Denture Base Material in Bucks spermatic cord. - Al-Dahhan., Muna Ridha (The Iraqi Journal of Veterinary Medicine, 2012)
This study was performed to identify gross and histopathology changes which can be occur in testis and spermatic cord following injection of Acrylic Dental Base Material inside spermatic cord , the agent is widely present ,cheep, quick ,highly solid and used as a substance of chemical castration. It was injected inside spermatic cord of 15 healthy adult bucks in the ratio of 3:1 bilaterally ; Treated animals where divided randomly in to 5 groups depending on time for gross and histopathology examination after injected with the material. Animals were followed up for 7 days, 14 days, 30 days, 60 days, and 150 days after injection. Result showed good and immediate hardening after 20-25 min. of injected material. Gross examination of testis after 7-14 days of material injection didn’t showed marked changes. While after 30 -60 days showed thickening of tunica vaginals which was easy isolated, and the testis was atrophied .And after 150 days showed disappear of testis structures with more atrophied. Histopathology changes of testis characterized by reduce rate of spermatogenesis , thickening of basement membrane ,inflammation was reduce in late stage and deposition of fibrous tissue . While the mean feature of histopathology changes of spermatic cord include, infiltration of inflammatory cells, then fibrosis which lead to complete contraction and obstruction of it from first week after injection